Twenty years of flexible exchange rates: Experiences and developments - Beate Reszat (Intereconomics, 1993)
The Bretton Woods system of fixed exchange rates was abandoned at the beginning of March 1973 when currencies were allowed to float. Has the system of flexible exchange rates fulfilled the expectations placed in it? How should experiences with regional systems of fixed exchange rates be assessed, and what are the prospects for a return to such a system worldwide?
Keywords: 330; Monetary Policy